2020
DOI: 10.3390/antiox9010042
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins from Hibiscus syriacus L. Inhibit Oxidative Stress-Mediated Apoptosis by Activating the Nrf2/HO-1 Signaling Pathway

Abstract: Hibiscus syriacus L. is distributed widely throughout Eastern and Southern Asia and considered as the national flower of South Korea. The extraction of several plant parts of H. syriacus L. is currently used as a natural remedy for several diseases, including breast and lung cancer, microbial infection, and chronic inflammation. However, the effect of the anthocyanin extract of H. syriacus L. petals (PS) in oxidative stress conditions has not been studied. In this study, we evaluated the cytoprotective effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Currently, the Nrf2/ARE signaling pathway appears to be the most important endogenous antioxidant stress pathway [65,66]. Furthermore, Nrf2 is pivotal in the host defense mechanism, and numerous key phase II enzymes, such as NQO1 and HO-1 [67], are controlled by Nrf2 transcription factor under ROS conditions [4].…”
Section: Effects On Cell Antioxidant Responsesmentioning
confidence: 99%
“…Currently, the Nrf2/ARE signaling pathway appears to be the most important endogenous antioxidant stress pathway [65,66]. Furthermore, Nrf2 is pivotal in the host defense mechanism, and numerous key phase II enzymes, such as NQO1 and HO-1 [67], are controlled by Nrf2 transcription factor under ROS conditions [4].…”
Section: Effects On Cell Antioxidant Responsesmentioning
confidence: 99%
“…Also, as mentioned above, the Nrf2/HO-1 signaling pathway plays an outstanding role in anti-oxidative activities after SCI [85,86]. Nrf2 was activated by oxidative stress after injury combined with antioxidant response elements [87] and increased its downstream anti-inflammatory and antioxidant enzymes, including HO-1 and NQO1 [86].In our study, we observed that Nrf2 was elevated after SCI, and Nrf2,HO-1 and NQO1were further increased by EA treatment combined with COG112, it could be easily predicted that Nrf2/HO-1 signaling pathway may function in oxidative stress after SCI and is involved with the effect of EA on the recovery of SCI.…”
Section: Discussionmentioning
confidence: 93%
“…It is also known that the level of NRF2 indicates the antioxidant capacity of the cells and its increase is linked with the enhanced ability to scavenge radicals [ 67 ]. Plants phenolic rich extracts were previously shown to exert a cytoprotective effect by increasing heme oxygenase-1 (HO-1) together with NRF2 [ 68 ]. In the current study, NRF2 activity was evaluated in HacaT normal skin cell line.…”
Section: Resultsmentioning
confidence: 99%